SORPTIVE STABILIZATION OF ORGANIC MATTER IN SOILS BY HYDROUS IRON OXIDES - Wagai R.; Mayer L.M. (My University, 2007)
Strong correlations between iron oxides (FeOx) and organic matter (OM) in soils have implied the importance of the former in stabilizing the latter. One mechanism thought to be important in this stabilization is sorption. We tested this possibility by reductively dissolving FeOx in a wide variety of soils and measuring the organic carbon (OC) that was solubilized. The OC dissolved from non-FeOx phases via anion exchange was corrected for by parallel control extractions. The resultant pool, reductively soluble OC, made up a minor amount of total soil OC in all but one of these soils, indicating that simple sorption reactions do not stabilize the bulk of soil OC in most mineral soils. OC:Fe ratios in the extracts from 2/3 of these soils were less than 0.22 (wt/wt), consistent with a sorbed state for this OC and showing that OC sorption by FeOx in these soils is limited by the amount of FeOx. The remaining soils had low pH and high OM concentrations; their higher OC:Fe ratios indicate inclusion of precipitated organo-Fe complexes in the extracts, which are likely only partially extracted by our method. The high volumetric ratios of OM to FeOx found in correlations between them from the literature are inconsistent with a dominant sorption control and point instead to stabilization to other mechanisms such as organo-Fe complexes or ternary associations among FeOx, OM and other minerals.
Keywords: CORRELATION; EXTRACTION METHOD; ION EXCHANGE; IRON OXIDE; ORGANIC CARBON; SOIL ANALYSIS; SOIL ORGANIC MATTER; SORPTION; STABILIZATION